Assertiveness and Self-esteem among Nurses Working at a Teaching Hospital, Bharatpur, Chitwan (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: In the nursing profession, assertiveness and self-esteem are essential components for effective patient care and therapeutic relationships. Lack of these components have been found to be a major problem in the nursing profession today. The objective of the study was to find out the level of assertiveness and self-esteem among nurses working at Teaching Hospital, Bharatpur, Chitwan.MATERIALS AND METHODS: A descriptive cross-sectional study design was conducted among 155 nurses working at Chitwan Medical College, Teaching Hospital, Bharatpur, Chitwan. Stratified proportionate simple random sampling technique was used to select sample. Data was collected by using standardized self-administered tool {Simple Rathus Assertiveness Schedule (SRAS) and Rosenberg Self-esteem Scale (RSES)} from 2078-11-29 to 2078-12-11. Data were analyzed by using descriptive and inferential statistics.RESULTS: The study revealed that more than half of the nurses (51.0%) have high assertiveness and more than half of the nurses (54.8%) have high level of self-esteem. There was statistically significant association between assertiveness and age (p=0.004), ethnicity (p